2018
DOI: 10.1097/md.0000000000010870
|View full text |Cite
|
Sign up to set email alerts
|

Outcome predictors in the management of intramedullary classic ependymoma

Abstract: This is a retrospective study.The aim of this study was to illustrate the survival outcomes of patients with classic ependymoma (CE) and identify potential prognostic factors.CE is the most common category of spinal ependymomas, but few published studies have discussed predictors of the survival outcome.A Boolean search of the PubMed, Embase, and OVID databases was conducted by 2 investigators independently. The objects were intramedullary grade II ependymoma according to 2007 WHO classification. Univariate Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(35 reference statements)
0
7
1
Order By: Relevance
“…Ependymoma is originated from the ependymal lining of the ventricular system or spinal canal, which may arise from anywhere along the ventricular system and spinal cord [2]. The World Health Organization (WHO) has classified ependymomas into 3 grades: Grade I; myxopapillary ependymoma and sub-ependymoma, Grade II; ependymoma and Grade III anaplastic ependymomas [3]. Although there is a long history of subclassifying ependymoma in histology, there is little treatment stratification for ependymomas and the long-term prognosis for patients with ependymoma remains barely understood [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ependymoma is originated from the ependymal lining of the ventricular system or spinal canal, which may arise from anywhere along the ventricular system and spinal cord [2]. The World Health Organization (WHO) has classified ependymomas into 3 grades: Grade I; myxopapillary ependymoma and sub-ependymoma, Grade II; ependymoma and Grade III anaplastic ependymomas [3]. Although there is a long history of subclassifying ependymoma in histology, there is little treatment stratification for ependymomas and the long-term prognosis for patients with ependymoma remains barely understood [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is inconsistent with the systematic review by Wang et al 54 The multivariate Cox model used to evaluate prognostic factors in spinal cord ependymomas showed that the extent of surgery did not increase OS (HR = 0.690, 95% CI = 0.119-3.977, P = .679). Wang et al 54 conducted an integrative analysis on grade II ependymomas and found that the extent of surgery did not have a statistical effect on OS. However, most previous reviews claimed that CR is associated with better outcomes.…”
Section: Discussioncontrasting
confidence: 72%
“…This result is consistent with a study conducted by Feldman et al, which reported no association between radiotherapy and overall tumor recurrence, regardless of the extent of resection. 52 Wang et al 54 also showed that adjuvant therapy could not improve outcomes after resection. However, Chen et al 51 reported that adjuvant radiotherapy positively affected PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Because recurrences can occur many years after the treatment, regardless of the EOR, long-term follow-up with MR is recommended. Older age, male sex, other than classical G2 pathological types (cellular, papillary, giant cell types) were found as negatively influencing the outcome (8,32,37,39,41).…”
Section: Spinal Ependymomasmentioning
confidence: 92%